Key Competencies in Social Work through Field Placement: Teaching and Learning Cases in Ukraine in the Time of COVID-19 (Journal of Comparative Social Work, 2021)
Field placement is considered a core component of social work education. However, it requires regular personal contacts with individuals, groups and communities. These contacts have been limited in the time of the COVID-19 pandemic. A central question is how to organize field placement during the lockdown to develop key competencies in social work. To answer this question, we employ the students’ reports, competency-based self-evaluation tools, students’ assessment of the field placement (led by the University’s education quality assurance centre) and assessment of students’ performance by the field placement supervisors and university instructors. This paper presents the achievements and challenges of teaching and mastering key competencies in social work at the School of Social Work of the National University of Kyiv-Mohyla Academy from different perspectives: students, placement agencies and the University itself. While almost all competencies have been taught and learned, those related to individual casework were the most difficult to achieve. The flexibility of the social work profession is also discussed in this paper. Future social workers should be flexible and meet the people's needs in different contexts, including lockdown. The findings have implications for students, schools of social work and field placement agencies.